Role of the Molecular Environment in Quenching the Irradiation-Driven Fragmentation of Fe(CO)5: A Reactive Molecular Dynamics Study - Andreides, Benjamin; Verkhovtsev, Alexey V; Fedor, Juraj; Solov'yov, Andrey V (The journal of physical chemistry. A, 2023)
Irradiation-driven fragmentation and chemical transformations of molecular systems play a key role in nanofabrication processes where organometallic compounds break up due to the irradiation with focused particle beams. In this study, reactive molecular dynamics simulations have been performed to analyze the role of the molecular environment on the irradiation-induced fragmentation of molecular systems. As a case study, we consider the dissociative ionization of iron pentacarbonyl, Fe(CO)5, a widely used precursor molecule for focused electron beam-induced deposition. In connection to recent experiments, the irradiation-induced fragmentation dynamics of an isolated Fe(CO)5+ molecule is studied and compared with that of Fe(CO)5+ embedded into an argon cluster. The appearance energies of different fragments of isolated Fe(CO)5+ agree with the recent experimental data. For Fe(CO)5+ embedded into an argon cluster, the simulations reproduce the experimentally observed suppression of Fe(CO)5+ fragmentation and provide an atomistic-level understanding of this effect. Understanding irradiation-driven fragmentation patterns for molecular systems in environments facilitates the advancement of atomistic models of irradiation-induced chemistry processes involving complex molecular systems.